A STUDY OF WORD OF MOUTH RELATED TO CONSUMER PURCHASE DECISION OF WOODEN FURNITURE ON LEILEM VILLAGE - Tamon, Irene Christine; Pangemanan, Sifrid S; Pandowo, Merinda (Universitas Sam Ratulangi, 2017)
Abstract: Purchasing decisions is the selection of a decision as an act of two or more alternative option. Here it is assumed that all voluntary behavior is based on the desire generated when consumers consciously and rationally choose one among alternative actions available. Consumer choice is Alternative the expected benefits and narrowing the options until the end of the selected alternative that can meet and satisfy the needs and desires. The purpose of this study is to analyze the relationship of words of mouth and customer purchasing decision on wooden furniture From Leilem. This research is conducted qualitatively. The result of this research is the words of mouth is related to the selling of wooden products from leilem and this study also found that most of the producers in leilem village are not really familiar with internet and other sophisticated e-marketing strategies, they do not even really have idea of how marketing works in their industry. This research could be a recommendation to other manufacturers to continuously improve the quality of their products and the way they interact with their customers. This study shows that the words of the mouth is very connected to the consumer's purchasing decision.Key words: words of mouth, purchasing decision, consumer behavior